2014
DOI: 10.1152/ajpregu.00371.2013
|View full text |Cite
|
Sign up to set email alerts
|

EUK-134 ameliorates nNOSμ translocation and skeletal muscle fiber atrophy during short-term mechanical unloading

Abstract: . EUK-134 ameliorates nNOS translocation and skeletal muscle fiber atrophy during short-term mechanical unloading. Am J Physiol Regul Integr Comp Physiol 306: R470-R482, 2014. First published January 29, 2014 doi:10.1152/ajpregu.00371.2013.-Reduced mechanical loading during bedrest, spaceflight, and casting, causes rapid morphological changes in skeletal muscle: fiber atrophy and reduction of slow-twitch fibers. An emerging signaling event in response to unloading is the translocation of neuronal nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(109 citation statements)
references
References 47 publications
(75 reference statements)
9
97
2
1
Order By: Relevance
“…These results have been confirmed by using antioxidant agents such as EUK-134 (SOD and catalase mimetic) [71] and SS-31 (mitochondria-targeted antioxidant) [54,121]. The inhibition of mitochondrial ROS production prevented soleus atrophy and UPS/autophagy activation induced by casting [54], whereas EUK-134 limited skeletal muscle atrophy and FOXO3a activation induced by hindlimb unloading [71]. Taken together, these data support that RONS activate UPS and autophagy in immobilization-induced skeletal muscle atrophy.…”
Section: Evidence For a Role Of Rons In Immobilization-induced Skeletmentioning
confidence: 59%
See 1 more Smart Citation
“…These results have been confirmed by using antioxidant agents such as EUK-134 (SOD and catalase mimetic) [71] and SS-31 (mitochondria-targeted antioxidant) [54,121]. The inhibition of mitochondrial ROS production prevented soleus atrophy and UPS/autophagy activation induced by casting [54], whereas EUK-134 limited skeletal muscle atrophy and FOXO3a activation induced by hindlimb unloading [71]. Taken together, these data support that RONS activate UPS and autophagy in immobilization-induced skeletal muscle atrophy.…”
Section: Evidence For a Role Of Rons In Immobilization-induced Skeletmentioning
confidence: 59%
“…A more restricted number of studies focused on the effects of immobilization on α,β-unsaturated aldehydes (e.g., 4-HNE, MDA), markers of lipid peroxidation. 4-HNE content increased in rat soleus after 8 days of hindlimb unloading [64,71], whereas elevations in MDA and TBARS contents were reported after 10 and 14 days of hindlimb unloading, respectively [61,69]. All together, these results suggest that immobilization first induced lipid peroxidation and later protein carbonylation in skeletal muscle.…”
Section: Skeletal Muscle Oxidative Stress In Immobilization and Physimentioning
confidence: 77%
“…Sarcolemmal nNOS was drastically mislocalized in aged plantaris muscle fibers, where it was observed predominately in the sarcoplasm. Previously, our group (Lawler and others 2014) and Suzuki et al (Suzuki and others 2007) found that mechanical unloading and denervation cause translocation of nNOSµ away from the sarcolemma. Mislocalization of nNOS is also noted in Duchenne muscular dystrophy (Brenman and others 1995) and other types of neuromuscular disorders (Finanger Hedderick and others 2011), further emphasizing the physiological importance of the protein for proper muscle function to occur.…”
Section: Discussionmentioning
confidence: 77%
“…Rather, Suzuki and colleagues report that muscle inactivity is associated with a dissociation of neuronal NO synthase (nNOS) from the dystroglycan complex and propose that the release of nNOS from the membrane results in nNOS activation and increased production of NO [7]. The finding that muscle disuse results in increased cytosolic nNOS has been confirmed by others [8, 27, 28]. Nonetheless, it is important to note that there are no published reports documenting higher NO production by non-membrane bound nNOS [29].…”
Section: Sources Of Ros and Rns In Atrophying Skeletal Musclementioning
confidence: 99%
“…Indeed, it is widely accepted that oxidative stress contributes to skeletal muscle atrophy due to both disease and prolonged muscle inactivity [3-6]. Further, evidence also links nitrosative stress to skeletal muscle atrophy resulting from chronic disease or prolonged muscle disuse [7, 8]. …”
Section: Introductionmentioning
confidence: 99%